2020
DOI: 10.1016/j.celrep.2020.107868
|View full text |Cite
|
Sign up to set email alerts
|

Theta Oscillations Coincide with Sustained Hyperpolarization in CA3 Pyramidal Cells, Underlying Decreased Firing

Abstract: Highlights d CA3 PC firing activity and membrane potential changes are brain state dependent d Coordinated, consistent hyperpolarization of CA3 PCs is time locked to theta events d Membrane potential changes are varied and transient during large irregular activity d Theta hyperpolarization and reduced variance are consistent with increased inhibition

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Similarly, in CA3 principal cells, activation of nAChRs by low concentration of nicotine enhances GABA release either directly ( Hajós et al, 2005 ) or indirectly, via NMDA receptors localized on GABAergic interneurons ( Mann and Mody, 2010 ; Wang et al, 2015 ). Furthermore, previous studies showed that brain states associated with high cholinergic activity and theta oscillations resulted in CA3 principal neuron inhibition via activation of interneurons ( Malezieux et al, 2020 ; Dannenberg et al, 2015 ). Thus, enhanced GABAergic tone may lead, as in CA1, to a reduced glutamate release from CA3 principal cells.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in CA3 principal cells, activation of nAChRs by low concentration of nicotine enhances GABA release either directly ( Hajós et al, 2005 ) or indirectly, via NMDA receptors localized on GABAergic interneurons ( Mann and Mody, 2010 ; Wang et al, 2015 ). Furthermore, previous studies showed that brain states associated with high cholinergic activity and theta oscillations resulted in CA3 principal neuron inhibition via activation of interneurons ( Malezieux et al, 2020 ; Dannenberg et al, 2015 ). Thus, enhanced GABAergic tone may lead, as in CA1, to a reduced glutamate release from CA3 principal cells.…”
Section: Discussionmentioning
confidence: 98%
“…Whole cell recordings in awake animals have opened a window to understanding the interplay between collective network activity and membrane potential (Vm) dynamics of hippocampal neurons which can reveal the nature and timing of synaptic inputs and subthreshold changes that are invisible to extracellular recordings. While recent efforts have examined the Vm of CA1 neurons around ripples (English et al, 2014;Hulse et al, 2016) and the Vm modulation by brain state across hippocampal subfields (Hulse et al, 2017;Malezieux et al, 2020), the subthreshold dynamics of CA3 pyramidal cells around ripples and the impact of cortical inputs on Vm behavior in CA3 remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not straightforward to relate the changes in calcium transient frequency that we observed to changes in AP patterns. Moreover, recent in vivo whole-cell recordings found that theta oscillations were associated with membrane potential hyperpolarization in most CA3 pyramidal neurons ( Malezieux et al, 2020 ), which could imply decreased average firing rates during running. However, theta periods included both resting and running periods and modulatory effects were quite heterogeneous across the CA3 population.…”
Section: Discussionmentioning
confidence: 99%
“…CA3 pyramidal neurons are special in forming an auto-associative recurrent network enabling memory encoding and pattern completion ( Rolls, 2007 ; Kesner and Rolls, 2015 ; Guzman et al, 2016 ; Knierim and Neunuebel, 2016 ). The functional properties of CA3 pyramidal neurons have been characterized largely with electrophysiology, using extracellular recordings ( Fox and Ranck, 1975 ; Csicsvari et al, 2000 ; Henze et al, 2002 ; Leutgeb et al, 2004 ; Frerking et al, 2005 ; Mizuseki et al, 2012 ; Oliva et al, 2016 ), in vivo intracellular and juxtacellular recordings ( Epsztein et al, 2011 ; Kowalski et al, 2016 ; Zucca et al, 2017 ; Diamantaki et al, 2018 ; Hunt et al, 2018 ; Malezieux et al, 2020 ), and whole-cell recordings in brain slices ( Jonas et al, 1993 ; Hemond et al, 2008 ; Hunt et al, 2018 ; Raus Balind et al, 2019 ). Pyramidal neurons in CA3 show properties distinct from CA1 ( Mizuseki et al, 2012 ; Oliva et al, 2016 ) but display heterogeneity within their population ( Hunt et al, 2018 ; Cembrowski and Spruston, 2019 ; Ding et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%